Empire's setting sun?: Patrick Blackett and military and scientific development of India - Anderson, Robert S. (2001)
It is difficult to give a measure of Patrick Blackett's wide-ranging influence in India. He had no official status in defence matters except as an advisor to Nehru. Since his consultations were not widely known, his public reputation, nor surprisingly, was largely in the field of scientific research institution building. In this capacity he advocated a realistic appraisal of the relations between the state and the military, and limitations on the military's growth and influence. It is not as a military consultant, however, but as an intervenor in scientific affairs and advisor to the research system that Blackett was and is best known in India. He came to understand its political-economy, specifically the political limits of the influence of the scientific community and the way in which very scarce economic resources were (or were not) mobilised within it. Blackett's objectives in India are enduring: to improve the working conditions of people doing research; to cut away the bureaucratic brambles which grow around the practice of research; to think carefully about the things which can be developed locally instead of being imported, to balance the state's insatiable desire for technical prestige with enhancing ordinary peoples' abilities to provide a better life for themselves. - Reproduced
Keywords: Blackett, Patrick; Scientific development - India; Scientific development